Holographic View of Mixed-State Symmetry-Protected Topological Phases in Open Quantum Systems - Shijun Sun; Jian-Hao Zhang; Zhen Bi; Yizhi You (PRX Quantum)
We establish a holographic duality between d-dimensional mixed-state symmetry-protected topological (mSPT) phases and (d+1)-dimensional subsystem symmetry-protected topological (SSPT) states. Specifically, we show that the reduced density matrix of the boundary layer of a (d+1)-dimensional SSPT state with subsystem symmetry S and global symmetry G corresponds to a d-dimensional mSPT phase with strong S and weak G symmetries. Conversely, we demonstrate that the wave function of an SSPT state can be constructed by replicating the density matrix of the corresponding lower-dimensional mSPT phase. This mapping links the density matrix in lower dimensions to the entanglement properties of higher-dimensional wave functions, providing an approach for analyzing nonlinear quantities and quantum information metrics in mixed-state systems. Our duality offers a new perspective for studying intrinsic mSPT phases that are unique to open quantum systems, without pure-state analogues. We show that strange correlators and twisted Rényi-N correlators can diagnose these nontrivial phases and we explore their connection to strange correlators in pure-state SSPT phases. Furthermore, we discuss several implications of this holographic duality, including a method for preparing intrinsic mSPT phases through the duality.